Gender unemployment catching-up: Empirical evidence from Italian regions - Marianna Belloc; Riccardo Tilli (Center for Economic Studies and ifo Institute (CESifo), 2010)
We study the persistence of the gender unemployment gap in the Italian regions in the 1992-2009 period. Results from unit-root tests analysis with structural break suggest that the process of gender catching-up in the unemployment rates is occurring in most of the regions but at different pace. Our findings indicate that there is substantial cross-region heterogeneity and the resulting picture does not match with that of a Center-North and South-and-Islands dichotomy in the Italian labour markets.
Keywords: C22; J16; J60; 330; gender unemployment gap; regional disparities; unit-root tests with structural break; Lohndifferenzierung; Geschlecht; Regionale Disparität; Unit Root Test; Strukturbruch; Schätzung; Italien